THE NEED TO DEVELOP SPIRITUAL AND EDUCATIONAL WORK IN HIGHER EDUCATION INSTITUTIONS - Turdiyev Ismoil Allayorovich (Web of Journals Publishing, 2025)
This article examines the need to develop spiritual and educational work in higher education institutions. Lexical meanings of a number of concepts "professional pedagogy" and "spiritual and educational" are given.
Keywords: Spirituality, student, enlightenment, teacher, education, upbringing, development